The Confused Professional Identity of Native and Non-Native EFL Teacher Educators: Are They Teachers or Researchers? - Adina Mannes (Athens Journal of Education, 2020)
The demands of teacher educators underwent a major change. They not only are required to excel in teaching, but also to conduct research as an essential part of their professional life. This ambivalence raises questions regarding their professional identity. How can they identify with their profession if their roles keep changing? Two native and two non-native EFL teacher educators were interviewed about their perception of professional identity regarding being a researcher or a teacher and whether the demand to excel relies also on personal background factors such as being a native English speaker. The results indicated tension between research and teaching, which is a cause of frustration for EFL teacher educators. As for the issue of personal background, most of the interviewees did not believe that such factors are crucial. However, everyday reality in their colleges, where there are more native than non-native English speaker teachers, shows otherwise.